Investigations on Integrated Funnel, Fan and Diffuser Augmented Unique Wind Turbine to Enhance the Wind Speed - K. Ramesh Kumar; M. Selvaraj (Journal of Applied Fluid Mechanics, 2023)
Wind energy is an alternative future energy to fossil fuels since it is abundant and green energy. As a result, high performance unique design is proposed that has a diffuser augmented wind turbine including intake funnel with guide vanes, natural fan, straight flow section, exit splitter with air openings and end flange. This proposed design is called as Integrated omni-directional Intake funnel, Natural fan, Straight diffuser, Splitter and Flange (I2NS2F) Design. To construct this I2NS2F configuration, four distinct wind turbines were developed: a) bare wind turbine, b) wind turbine diffuser design with single rotor turbine, c) bend diffuser, intake funnel, natural fan, splitter and flange and d) I2NS2F design. The proposed designs are numerically studied using MATLAB Simulink and Ansys Fluent. These designs are optimized by Random Search Optimization with Supervisory Control and Data Acquisition technique to evaluate the wind velocity and the performance is comparatively estimated. From this analysis, I2NS2F design achieves 53m/s of wind velocity at turbine region for 5.5m/s inlet wind and it could be considered as highest wind velocity than other three designs. It is evidently proved and concluded that proposed I2NS2F design augments natural wind, resulting in greater green power generation.